Socio-Cultural Adaptation and Academic Achievement: A Case Study of International Students at Prince of Songkla University, Pattani Campus - Maharani, Else Shinta; M. Kaba, Abdulai; Syariful, Syariful (Jurnal Multidisiplin Indonesia, 2024)
The aim of this research is to obtain an overview and explanation of the socio-cultural adaptation process of international students at Prince Songkla University, Pattani Campus. Apart from that, to explain students' academic achievements. This research is about socio-cultural adaptation and academic achievement of International Students at Prince of Songkla University, Pattani Campus, using quantitative methods with a descriptive approach. In this research, the sample was determined using a saturated sampling technique, where this technique was chosen if all members of the population were used as the research sample. Because the population of this study was no more than 100, the researcher took the entire population as the research sample. So, the sample for this research is 41 International Students at PSU Pattani Campus. consisting of 36 international students and 5 international exchange students. For this research, a questionnaire will be used to carry out measurements using a Likert Scale. This research describes the socio-cultural adaptation process of international students at Prince of Songkla University, Pattani Campus. The results of this research show that there is a positive and significant influence between students' socio-cultural adaptation and the academic achievement of international students at PSU of 0.032 which means it is smaller than 0.05 (0.032 < 0.05) with a coefficient value of 0.543 which has a positive sign so it can be concluded that The hypothesis is accepted that socio-cultural adaptation can improve the academic achievement of international students at PSU.